2019
DOI: 10.1007/s11705-019-1838-8
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid modified Pt/C electrocatalysts for cathode application in proton exchange membrane fuel cells

Abstract: The modification of Pt/C catalyst by using ionic liquids to improve their catalyst activities has been reported by many researchers, but their practical behavior in operating fuel cells is still unknown. In this work, we study the ionic liquid modified Pt/C nanoparticle catalysts within cathodes for proton exchange membrane fuel cells. The influence of the ionic liquid amount, adsorption times and dispersing solvents are investigated. The experiment results show the best performance enhancement is achieved thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…[ 12,13,32,73 ] IL modification of a commercial Pt/C catalyst in PEMFCs confirmed that the presence of the IL can induce a significant increase in activity. [ 12 ] Modification of the pristine catalyst with 2% IL increased the peak power density from 0.34 to 0.61 W cm −2 (Figure 7a). [ 12 ] Zhang et al did also study the effect of IL loading, observing the typical maximum behavior of activity as a function of IL coverage.…”
Section: Solid Catalysts With An Il Layermentioning
confidence: 94%
See 4 more Smart Citations
“…[ 12,13,32,73 ] IL modification of a commercial Pt/C catalyst in PEMFCs confirmed that the presence of the IL can induce a significant increase in activity. [ 12 ] Modification of the pristine catalyst with 2% IL increased the peak power density from 0.34 to 0.61 W cm −2 (Figure 7a). [ 12 ] Zhang et al did also study the effect of IL loading, observing the typical maximum behavior of activity as a function of IL coverage.…”
Section: Solid Catalysts With An Il Layermentioning
confidence: 94%
“…Later on, synthetic procedures have been introduced that allow for controlled and smaller loading of ILs. They consist of the dilution of the catalyst and the desired amount of IL in isopropanol, [ 13,29,31,13–13 ] ethanol, [ 12 ] or ethanol/water mixtures, [ 33 ] generally followed by mixing, sonication, and evaporation. Du and coworkers utilized 10 min sonication, followed by 3 h of magnetic stirring, partial solvent evaporation by vacuum desiccation, and centrifugation to isolate the catalyst.…”
Section: Solid Catalysts With An Il Layermentioning
confidence: 99%
See 3 more Smart Citations